Securing the smart grid: threats and remediation. (2016) - Chalmers, Carl; Mackay, Michael; MacDermott, Aine
The implementation of the smart grid brings many improvements over the traditional energy grid by leveraging a vast interconnected infrastructure that allows two way communication and automation throughout the entire grid. A key difference over the existing grid is the introduction of the advanced metering infrastructure (AMI) which contains many new components such as the smart meter and the communication gateways. The focus of this paper is to examine the possible effects on the energy supply should these devices become compromised. Smart meters are one of the most important components in the smart grid implementation which allow a real time flow of information to/from the consumer on their energy usage. The paper also discusses how closing coal and oil power plant has increased our demand on gas power stations in the UK. Our experiments show that manipulating smart meter readings can create a massive shortfall in gas provisioning.